Kolozsvár és az egyetem az első világháború éveiben - Toth, Szilárd (Per Aspera ad Astra, 2018)
The inhabitants of Kolozsvár, like the inhabitants of the other cities of the Austro- Hungarian Monarchy, or like the bourgeoisie from other cities from Europe, received the outbreak of World War I with great enthusiasm. At the beginning of the 20th century, there were no televisions and radio stations, and the entertainment facilities were more limited compared to today’s and the outbreak of a war was considered a world sensation. It brought something new in the „gray everyday life”, there was something to talk about, there was a reason waiting for the fresh news in the newspapers. To men, especially young officers, opened the opportunity to advance rapidly in military careers, and at the same time facing the life threats could bring them glory, increasing their chances of winning the hearts of young ladies. And, of course, everyone was certain of victory and of surviving the war. Soon, however, the inflation associated with the war knocked on Kolozsvár, and dearth years came. The purpose of this study is to analyze the impact of the World War I on the city and the university. I analyzed the economic and social impact of war on both the city and the university. It was clear that the war had not only negative but also positive effects: it encouraged the service sector, trade, promoted female emancipation, boosted the film production, at the University was established the Department of Orthopedics, etc. But despite all this, it had a number of negative effects on the population of the city: war victims, the decline of the living standards, the increase of the rate of criminality, the damage of the buildings of the university and the city as well, etc. There is still much to discover for the researchers on this topic, and my humble attempt will hopefully inspire those interested in this topic.